Seasonal variation of hepatitis A virus infection in the city of Rio de Janeiro, Brazil - Livia Melo VILLAR; Vanessa Salete DE PAULA; Ana Maria Coimbra GASPAR (Revista do Instituto de Medicina Tropical de São Paulo, 2002)
Hepatitis A virus (HAV) infection constitutes a major public health problem in Brazil. The transmission of HAV is primarily by fecal-oral route so the water is an important vehicle of HAV dissemination. There is a great incidence of acute cases of hepatitis A in some areas of Brazil however the seasonal variation of these cases was not documented. The aim of this study was to determine the seasonality of HAV infection in Rio de Janeiro. From January 1999 to December 2001, 1731 blood samples were collected at the National Reference Center for Hepatitis Viruses in Brazil (NRCHV). These samples were tested by a commercial enzyme-immunoassay to detect anti-HAV IgM antibodies. Yearly positive rates were 33.74% in 1999, 32.19% in 2000, and 30.63% in 2001. A seasonal variation was recognized with the highest incidence in spring and summer. Furthermore a seasonal increase in incidence of HAV infection was found during the rainy season (December to March) because the index of rains is very high. It is concluded that HAV infections occur all year round with a peak during hot seasons with great number of rains.